Kebijakan Pemerintah Daerah dalam Kerja Sama Program dan Pendanaan Bagi Pesantren - Yusdianto; Rohaini; Fazry Maulana; Ahmad Zazili; Ade Firmansyah (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the internal sovereignty of the Indonesian government in the implementation of cooperation in Islamic boarding school funding programs as regulated in Article 46 of Law Number 18 of 2019 concerning Islamic Boarding Schools. to find out what challenges and obstacles the government faces in maintaining internal sovereignty in the Islamic boarding school funding program, to find out how to implement Article 46 of the Islamic boarding school law from the perspective of state sovereignty. This study uses a normative juridical method with a statutory and conceptual approach. The results of the study indicate that the implementation of the Islamic boarding school funding program based on Article 46 of the Islamic Boarding School Law requires a balance between openness to external funding sources and protection of the government's internal sovereignty in determining the direction of Islamic boarding school education policy. The main challenges identified include the potential for foreign interest intervention, financial dependence, and harmonization of funding policies with the characteristics and independence of Islamic boarding schools. This study recommends strengthening the supervisory mechanism, preparing comprehensive derivative regulations, and a funding cooperation model that focuses on strengthening the autonomy and independence of Islamic boarding schools.